Cardiac Myxoma among Patients Undergoing Cardiac Surgery in a Tertiary Care Center: A Descriptive Cross-sectional Study - Prabhat Khakural; Ravi Baral; Anil Bhattarai; Bhagawan Koirala (Journal of Nepal Medical Association, 2022)
Introduction: Heart neoplasms are rare tumors. Myxoma is the commonest primary benign tumor of the heart presenting with features of obstruction, arrhythmia, and embolism. Surgical excision of the tumor is the gold standard of treatment. The aim of the study is to find out the prevalence of cardiac myxoma among all cardiac surgeries operated during the study period.